Directed Evolution of a Halide Methyltransferase Enables Biocatalytic Synthesis of Diverse SAM Analogs. Issue 3 (12th November 2020) - Tang, Qingyun; Grathwol, Christoph W.; Aslan‐Üzel, Aşkın S.; Wu, Shuke; Link, Andreas; Pavlidis, Ioannis V.; Badenhorst, Christoffel P. S.; Bornscheuer, Uwe T.
Abstract: Biocatalytic alkylations are important reactions to obtain chemo‐, regio‐ and stereoselectively alkylated compounds. This can be achieved using S‐adenosyl‐l ‐methionine (SAM)‐dependent methyltransferases and SAM analogs. It was recently shown that a halide methyltransferase (HMT) from Chloracidobacterium thermophilum can synthesize SAM from SAH and methyl iodide. We developed an iodide‐based assay for the directed evolution of an HMT from Arabidopsis thaliana and used it to identify a V140T variant that can also accept ethyl‐, propyl‐, and allyl iodide to produce the corresponding SAM analogs (90, 50, and 70 % conversion of 15 mg SAH). The V140T AtHMT was used in one‐pot cascades with O ‐methyltransferases (IeOMT or COMT) to achieve the regioselective ethylation of luteolin and allylation of 3, 4‐dihydroxybenzaldehyde. While a cascade for the propylation of 3, 4‐dihydroxybenzaldehyde gave low conversion, the propyl‐SAH intermediate could be confirmed by NMR spectroscopy. Abstract : Biocatalytic alkylations are valuable for late‐stage functionalization but are limited by the availability of S ‐adenosyl‐l ‐methionine analogs. Directed evolution was used to create an engineered halide methyltransferase capable of converting cheap and readily available alkyl iodides into a number of SAM analogs. Used in cascades with methyltransferases, this enables chemo‐, regio‐ and stereoselective alkylations which are difficult to achieve by chemical means.